2016
DOI: 10.1002/ccd.26526
|View full text |Cite
|
Sign up to set email alerts
|

Early catheterization after initiation of extracorporeal membrane oxygenation support in children is associated with improved survival

Abstract: Cardiac catheterization and transcatheter interventions on ECMO can be performed with low rate of complications. Catheterization was associated with high rate of interventions. Better survival to hospital discharge was associated with transcatheter interventions, earlier performance of catheterization after ECMO and diagnosis of CM. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 31 publications
(49 reference statements)
1
31
1
Order By: Relevance
“…Another retrospective review of 75 catheterizations in pediatric ECLS patients found that the mean ECMO‐to‐catheterization time was shorter in survivors than non‐survivors (1.6 vs. 3.5 days). However, the inclusion of a large number of patients with cardiomyopathy as well as referrals for left atrial decompression may confound these results . Finally, an analysis of 49 catheterizations in pediatric cardiac patients found that those receiving catheterization within 48 hours of ECLS initiation demonstrated less respiratory complications and improved 30‐day survival in comparison to those receiving catheterization beyond 48 hours of ECLS initiation .…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective review of 75 catheterizations in pediatric ECLS patients found that the mean ECMO‐to‐catheterization time was shorter in survivors than non‐survivors (1.6 vs. 3.5 days). However, the inclusion of a large number of patients with cardiomyopathy as well as referrals for left atrial decompression may confound these results . Finally, an analysis of 49 catheterizations in pediatric cardiac patients found that those receiving catheterization within 48 hours of ECLS initiation demonstrated less respiratory complications and improved 30‐day survival in comparison to those receiving catheterization beyond 48 hours of ECLS initiation .…”
Section: Discussionmentioning
confidence: 99%
“…Residual lesions can be identified and, sometimes, addressed via cardiac catheterization. Abraham et al, showed that survival was significantly better with transcatheter interventions compared with no intervention in patients with congenital heart disease . Major catheter complications, requiring surgical intervention, occurred in 7% of catheterizations, no complications occurred during transport, and survival improved if catheterization was done early in the ECMO course (1.6 vs 3.5 days).…”
Section: Discussionmentioning
confidence: 99%
“…If the patient cannot be weaned off ECLS due to hemodynamic problems, cardiac catheterization should be performed urgently. In a prior study, an 83% survival to discharge rate was reported in pediatric cardiac ECLS patients following catheterization . In this group, 6.7% suffered from major procedural complications.…”
Section: Discussionmentioning
confidence: 82%
“…Postoperative ECLS provides a temporary stabilization of hemodynamics. During this period, clarifying the underlying problem is very important . If the patient cannot be weaned off ECLS due to hemodynamic problems, cardiac catheterization should be performed urgently.…”
Section: Discussionmentioning
confidence: 99%